1987
DOI: 10.1113/jphysiol.1987.sp016619
|View full text |Cite
|
Sign up to set email alerts
|

Control of end‐plate channel properties by neurotrophic effects and by muscle activity in rat.

Abstract: SUMMARY1. The formation of ectopic neuromuscular synapses was induced in rat soleus muscle by implantation of the fibular nerve into the proximal part of the muscle and subsequent sectioning of the soleus nerve. The gating properties of acetylcholine (ACh) receptors at the newly formed end-plates were examined by analysis of acetylcholine-induced membrane current fluctuations.2. In agreement with earlier studies, the apparent mean open time of end-plate channels decreased during synaptic development from about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 39 publications
(66 reference statements)
1
14
0
Order By: Relevance
“…Noise analysis combined with calculations of ACh diffusion and comparison of junctional vs. extrajunctional AChR numbers suggest that fetal AChRs are inserted into the denervated end-plate membrane in inactive muscle. As with the same method, adult junctional channels can be readily resolved at denervated rat end-plates (Brenner & Sakmann, 1983) and at ectopic end-plates formed by TTX-blocked nerves in inactive muscles whose extrajunctional ACh sensitivity is comparable to that of denervated muscles (Cangiano, 1985;Brenner et al 1987), it seems unlikely that a significant population of junctional adult AChRs could have been missed in our experiments. Thus, fetal AChRs must be contained in the denervated end-plate membrane.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Noise analysis combined with calculations of ACh diffusion and comparison of junctional vs. extrajunctional AChR numbers suggest that fetal AChRs are inserted into the denervated end-plate membrane in inactive muscle. As with the same method, adult junctional channels can be readily resolved at denervated rat end-plates (Brenner & Sakmann, 1983) and at ectopic end-plates formed by TTX-blocked nerves in inactive muscles whose extrajunctional ACh sensitivity is comparable to that of denervated muscles (Cangiano, 1985;Brenner et al 1987), it seems unlikely that a significant population of junctional adult AChRs could have been missed in our experiments. Thus, fetal AChRs must be contained in the denervated end-plate membrane.…”
Section: Discussionmentioning
confidence: 65%
“…Specifically, it stimulates the increase of junctional AChR accumulations (L0mo, et al 1984) and it promotes the expression of adult AChRs at developing neonatal and ectopic rat (Brenner et al 1987;Brenner, 1988) and mouse end-plates (unpublished). Our present data suggest that besides the differential resistance of eand y-subunit mRNA to activity, one mechanism contributing to these effects is its stabilizing action on junctional AChRs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the disappearance of IK(d) occurred at a time when synaptogenesis was nearly completed these two processes may be independent of each other. It was previously reported that synaptogenesis regulates the maturation of Ca2+ (Gonoi & Hasegawa, 1988) and neurotransmitter-activated channels (Brenner, L0mo & Williamson, 1987); therefore, future experiments should address whether synaptogenesis can also modulate K+ channels in the pineal gland. The final factor that needs to be considered, since it may also influence the shape of the cell's response, is the significant degree of developmental cell death which occurs in the pineal gland during the first few weeks after birth .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is widely accepted that neural factors and electrical activity regulate AChR gene expression (for review, see Laufer and Changeux, 1989;Changeux et al, 1990), their respective roles in promoting the conversion from the embryonic to the adult forms of the AChR are still far from clear (Brenner et al, 1987;Brehm and Henderson, 1988). In vivo studies in rats have suggested that the conversion of embryonic to adult AChR results from a 'priming influence' from the motor nerve (Brenner, 1988; Gu and Hall, 1988;Brenner et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Our attempts to replace the feeder layer by purified attachment factors Laufer and Changeux;Changeux et al, 1990). Muscle electrical activity has also been reported to regulate channel conversion (Brenner et al, 1987;Brenner, 1988). In primary cultures of chick and rat myotubes which display spontaneous contractile activity, a down-regulation of surface AChR occurs (Cohen and Fischbach, 1973;Rubin, 1985;Osterlund et al, 1989).…”
Section: Introductionmentioning
confidence: 99%